Pengembangan Media Pembelajaran Maharah Qiro’ah Berbasis Edutainment Dengan Bantuan Website Socrative - Adlina Atthohiro, Nyayu Nadida; Wasilah; Muhammad, Kemas (Ukazh: Journal of Arabic Studies, 2025)
Maharah Qira'ah learning often faces technical challenges, such as difficulties in vocabulary comprehension and text reading. This can be caused by a lack of innovation in the use of learning media and engaging approaches. This research aims to develop Maharah Qira'ah learning media based on Edutainment with the assistance of Socrative to create a more enjoyable and interactive learning experience, thereby increasing students' interest and reading skills. The research method used is the Research and Development (R&D) model Borg and Gall, including needs analysis, planning, product development, expert validation, trial, and refinement. Through a student needs questionnaire with a percentage of 72.997%, it was stated that students needed the development of new media and approaches. The results of media expert validation showed a percentage of 90% (very feasible), and material expert validation showed a percentage of 91.42% (very feasible). This proves that the Socrative media developed with an Edutainment approach is very feasible to be used as Maharah Qira'ah learning media at SMA Muhammadiyah 6 Palembang. The implication of this research is the creation of innovative learning media that can enhance students' abilities and interest in Maharah Qira'ah learning.